2014
DOI: 10.1037/h0098949
|View full text |Cite
|
Sign up to set email alerts
|

Depression in homeless mothers: Addressing an unrecognized public health issue.

Abstract: Homeless mothers experience disproportionately high rates of major depressive disorder compared with the general population. Stressed by their circumstances, these women struggle to protect their families. Children living with a depressed parent have poorer medical, mental health, and educational outcomes. Despite the adverse impact on children, depression among mothers experiencing homelessness remains unacknowledged, unrecognized, and untreated. This article reviews the evidence supporting preventive and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
58
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 61 publications
6
58
1
Order By: Relevance
“…Women's internalizing issues are common antecedents of homelessness, particularly when combined with low levels of education, unemployment, and poor health (Bassuk et al, 1998;Rog & Buckner, 2007). However, the adverse mental and emotional experiences of homeless women are often unrecognized, undiagnosed, and untreated (Bassuk, 2007;Bassuk & Beardslee, 2014). said that single mothers live impossible lives and found that more than 90% of homeless single mothers have experienced severe physical or sexual abuse (see also Vostanis, 2002).…”
Section: Internalizing Factorsmentioning
confidence: 97%
See 1 more Smart Citation
“…Women's internalizing issues are common antecedents of homelessness, particularly when combined with low levels of education, unemployment, and poor health (Bassuk et al, 1998;Rog & Buckner, 2007). However, the adverse mental and emotional experiences of homeless women are often unrecognized, undiagnosed, and untreated (Bassuk, 2007;Bassuk & Beardslee, 2014). said that single mothers live impossible lives and found that more than 90% of homeless single mothers have experienced severe physical or sexual abuse (see also Vostanis, 2002).…”
Section: Internalizing Factorsmentioning
confidence: 97%
“…Among homeless mothers, half report fewer than three people they could count on for support and close to 15% of these mothers indicate their children serve as their only support network (Letiecq, Anderson, & Koblinsky, 1998;Zima et al, 1996). The combination of economic adversity, residential instability, and poorer maternal mental health is linked with a host of adverse outcomes for children in homeless families (Bassuk & Beardslee, 2014).…”
Section: Internalizing Factorsmentioning
confidence: 99%
“…On a given night in 2014, approximately 20% of the homeless population had a serious mental illness (U.S. Department of Housing and Urban Development, 2015a), and several studies have found high rates of co-occurring disorders (Fazel et al, 2008;Fazel, Geddes, & Kushel, 2014;Torchalla et al, 2011;Bassuk, Buckner, Perloff, & Bassuk, 1998;North & Smith, 1992). Among homeless mothers, rates of posttraumatic stress disorder (PTSD) range from 22% to 33% (U.S. Department of Housing and Urban Development, 2015b, Bassuk et al, 1998;Hayes, Zonneville, & Bassuk, 2013), while lifetime rates of depression range from 45% to 85% (Bassuk et al, 1996;Bassuk et al, 1998;Weinreb, Buckner, Williams, & Nicholson, 2006;Bassuk & Beardslee, 2014). In one study of homeless families, 63% of mothers had a co-occurring substance use disorder and PTSD, and 85% had both a substance use disorder and depression (Hayes et al, 2013).…”
mentioning
confidence: 97%
“…In addition, women living with IPV must grapple with sometimes overwhelming concerns: protecting their children, ensuring that basic survival needs such as food and shelter are met, and managing feelings of shame and isolation (Thompson et al, 2000). It is not surprising that homeless women who experience extreme poverty, violence, and limited support networks have high rates of depression (Bassuk & Beardslee, 2014).…”
mentioning
confidence: 99%